2001
DOI: 10.1038/sj.ijo.0801733
|View full text |Cite
|
Sign up to set email alerts
|

Fat content in individual muscle fibers of lean and obese subjects

Abstract: OBJECTIVE: To examine skeletal muscle intracellular triglyceride concentration in different fiber types in relation to obesity. DESIGN: Skeletal muscle fiber type distribution and intracellular lipid content were measured in vastus lateralis samples obtained by needle biopsy from lean and obese individuals. SUBJECTS: Seven lean controls (body mass index (BMI) 23.0 AE 3.3 kg=m 2 ; mean AE s.d.) and 14 obese (BMI 33.7 AE 2.7 kg=m 2 ) individuals; both groups included comparable proportions of men and women. MEAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
152
3
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(184 citation statements)
references
References 29 publications
22
152
3
6
Order By: Relevance
“…Similar findings were previously reported for Biceps muscles of Yucatan swine on a "Western"-type diet (14). These data correlate well with previous studies in humans showing that skeletal muscles from obese compared with lean individuals have greater muscle CSAs (9,24). The increased CSAs could have a negative effect on the oxygen and substrate supply to the center of the fiber, leading to the reduced muscle performance.…”
Section: E853supporting
confidence: 81%
See 3 more Smart Citations
“…Similar findings were previously reported for Biceps muscles of Yucatan swine on a "Western"-type diet (14). These data correlate well with previous studies in humans showing that skeletal muscles from obese compared with lean individuals have greater muscle CSAs (9,24). The increased CSAs could have a negative effect on the oxygen and substrate supply to the center of the fiber, leading to the reduced muscle performance.…”
Section: E853supporting
confidence: 81%
“…Increased fiber size could diminish oxygen and substrate supply for the metabolic processes in the central area of the fiber. Skeletal muscles from obese compared with lean individuals had greater muscle cross-sectional areas (CSAs) of both type 1 and 2 fibers (9,24). Weight loss resulted in a 14 -25% decrease of the fiber CSAs of both type 1 and type 2 muscle fibers (12), supporting the idea that obesity correlates with an increase in muscle fiber area.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…In both obese and lean subjects, it has been shown that the IMTG content is the greatest in the oxidative type I and the lowest in the glycolytic type II muscle fibres. 34 Interestingly, it is the oxidative type I fibres which are the most insulin sensitive. 35 When comparing the divergent conditions of obesity and ETr, an apparent inconsistency exists in the relationship between IMTG and insulin sensitivity.…”
Section: Association Between Insulin Resistance and Imtg Contentmentioning
confidence: 99%